Circulatory [food] systems: Icelandic bloodmaring, reproductive technologies, and the porosity of female agricultural bodies - Lally, Anne (Cuizine, 2018)
The integration of bloodmaring, the industry of harvesting blood from pregnant horses for the synthesis of equine chorionic gonadotropin (eCG), into Icelandic agricultural forms exposes tenuous interconnections of agrarian life, supply chains, and market interests. Corporealities and biotechnology are intertwined intimately, creating strange bedfellows spanning species, lifeways, nations, and economies within the bucolic landscape of rural Iceland. Governed by biopharmaceutical supply chains, raw resources are obscured from the final medicalized product; a quagmire of interspecies sub-contractors flow through sterilized vials, condensing in the reproductive systems of livestock in North America. Within these networks, female bodies are commoditized and technologized, fused together, and manipulated to exploit their reproductive capacities on an international scale. This paper travels international agricultural networks by tracing the veins on a mare’s neck to the circuits through which blood is reformulated into a biopharmeceutical product biologically recycled in the bodies of other livestock. Engaging feminist theory on new materialisms, science studies, and human and nonhuman animal relationships, this paper provides a multispecies ethnography of bloodmaring by exploring female agricultural bodies ensnared and enlivened via food production supply chains.